Photoresponse from single upright-standing ZnO nanorods explored by photoconductive AFM - Beinik, Igor; Kratzer, Markus; Wachauer, Astrid; Wang, Lin; Piryatinski, Yuri P.; Brauer, Gerhard; Chen, Xin Yi; Hsu, Yuk Fan; Djurišić, Aleksandra B.; Teichert, Christian (Beilstein Journal of Nanotechnology, 2013)
Background: ZnO nanostructures are promising candidates for the development of novel electronic devices due to their unique electrical and optical properties. Here, photoconductive atomic force microscopy (PC-AFM) has been applied to investigate transient photoconductivity and photocurrent spectra of upright-standing ZnO nanorods (NRs). With a view to evaluate the electronic properties of the NRs and to get information on recombination kinetics, we have also performed time-resolved photoluminescence measurements macroscopically.Results: Persistent photoconductivity from single ZnO NRs was observed for about 1800 s and was studied with the help of photocurrent spectroscopy, which was recorded locally. The photocurrent spectra recorded from single ZnO NRs revealed that the minimum photon energy sufficient for photocurrent excitation is 3.1 eV. This value is at least 100 meV lower than the band-gap energy determined from the photoluminescence experiments.Conclusion: The obtained results suggest that the photoresponse in ZnO NRs under ambient conditions originates preferentially from photoexcitation of charge carriers localized at defect states and dominates over the oxygen photodesorption mechanism. Our findings are in agreement with previous theoretical predictions based on density functional theory calculations as well as with earlier experiments carried out at variable oxygen pressure.
Keywords: AFM; nanorods; photoconductive AFM; photoconductivity; ZnO